Appearance‐based vs health‐based sun protective messages: A randomized, double‐blind controlled study. (23rd September 2018) - Cheng, Judy; Widjajahakim, Rafael; Rajanala, Susruthi; B. C. Maymone, Mayra; Secemsky, Eric; Vashi, Neelam A.
Summary: Background: Appearance‐based messages have shown promise in improving sun protection habits among Caucasians but have scarcely been investigated in Hispanic populations. Objective: To compare the effectiveness of appearance‐based vs health‐based messages in an ethnic patient population, where hyperpigmentation disorders are prevalent and often cosmetically concerning. Methods: One hundred thirty‐seven patients were randomized to receive images of (a) skin cancer, (b) hyperpigmentation, or (c) wrinkles. Analysis of variance tests for repeated measures were used to estimate the effects of the different stimuli on participants' knowledge and intention to sun protect. Results: Appearance‐based interventions were more effective in improving intentions to sun protect among both Hispanics and non‐Hispanic Whites ( P < 0.05). They were furthermore more effective among younger patient populations (≤40 years old) and patients who thought that a tanned appearance is attractive ( P < 0.05). Conclusions: Appearance‐based photos of sun damage were more effective than health‐based messages among Hispanics, younger patient populations, and those who find tanned appearances to be attractive.